Human Rights of Men in the World of Globalization-An Essence of Time: A Critical Appraisal - Dr. Ramesh kumar; Rohit Kumar Verma (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2022)
The life, liberty, and security of men cannot be given into the hands of women as a puppet in the Rule of Law under the conception of human rights, bearing in mind the “abuses of the law, preconceived ideology, predefined consequences and others against men, subjecting to exceptions.” Men have also the universal, inherent inalienable, and natural human right to life with dignity and security. In today’s changing globalized scenario, the human rights of men have become the need of the hour and essence of time by reason of arbitrary deprivation and denial of human rights. This research has no intention against women’s human rights and feminism in any case and circumstance. Gender neutrality is required in today’s context for certain matters as to human rights otherwise than some exceptions and exclusions in accordance with the time, necessity, circumstances, and others in this regard This research has especially emphasized the specification of human rights of men in a global perspective. This research has emphasized the human rights of men in the world of globalization as an essence of time as available.